HUBUNGAN ASUPAN MAKANAN ASAM LEMAK OMEGA 3;6 TERHADAP MEMORI JANGKA PENDEK ANAK SEKOLAH DASAR ISLAM AL-AZHAR 21 PONTIANAK TAHUN 2014 - ., Neneng Wulandari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background : Omega-3 and omega-6 fatty acids are the important essential fatty acids for children brain. Essential fatty acids play animportant role in biochemical process of human brain. Good short termmemory ability is important for school age children in order to improve theiracademic achievement. There is no other research conducted thecorrelation between intake of omega 3;6 fatty acids and short termmemory in Islamic elementary school student of Al-Azhar 21 Pontianak.Objective : This research aims to find whether there is correlationbetween intake of omega 3;6 fatty acids and short term memory in Islamicelementary school student of Al-Azhar 21 Pontianak. Method : This is ananalytic study with cross-sectional approach. Sixty three participants arerecruited using non-probability sampling (consecutive sampling) technique.Measurement was taken including subject’s height and weight. Short termmemory test was evaluated by digit span from Wechsler-BellevueIntelligence Scale for Children. Result : There is no significant correlationbetween intake of omega 3;6 fatty acids and short term memory(p=0,203). Conclusion : Intake of omega 3;6 fatty acids is not a primaryfactor of increasing children short term memory, there are the othersfactors like iron, stimulation, omega 3;6 during pregnancy, history ofexclusive breastfeeding and children’s age which support the increasing ofshort term memory. KEYWORDS: Intake of omega-3 and omega-6, Short term memory